USE OF ACTIVE PRINCIPLES IN GRAPES, IN MEDICAL FIELD - Irinel Lungu; Dorin Ioan Cocoș; Monica Dinu; Cristina Bazbanela (Romanian Dental Association for Education, 2023)
This paper aims a review, the main active principles obtained from the extraction of Fructus Vinifera (grapes). Vitis Vinifera (grapes) contains several active principles, including flavonoids, polyphenols, anthocyanins, proanthocyanidins, procyanidins, and stilbene resveratrol derivatives. In this review, we summarize the active constituents of grapes and their pharmacological effects, including antioxidants, anticancer, and antibacterials on the pathogen Streptococcus mutants and antidiabetics, in published experimental studies. In recent years, active constituents found in seeds, fruits, stems, skin, and grape pomace have been identified, and some have been studied extensively. Resveratrol (3,5,4'-trihydroxy-trans-stilben; RV), a food constituent found in grapes and wine, exerts a wide variety of pharmacological activities. The novelty of the paper refers to the properties of resveratrol, respectively to the action of cancer chemoprevention due to the inhibitory action of protein 1 associated with metastases (MTA1). This review seeks to provide a brief overview of pharmacological, toxicological and clinical studies of grapes and their active components, in particular resveratrol.